GENETICS OF COTYLEDON COLOUR IN LENTIL (Lens culinaris medik.) - YOGESH KUMAR,; JITENDRA KUMAR,; SUSHIL KUMAR CHATURVEDI, (The Bioscan, 2018)
The genetics (inheritance) of cotyledon colour in lentil was studied on the basis of segregation patterns (monogenic, digenic and trigenic) observed in the F1, F2 and F3 generations derived from 36 different crosses involved 31 parents. A monogenic inheritance pattern of cotyledon colour was obtained in the F2 generation when analysed of orange  yellow, orange  brown orange  dark green and yellow  light green crosses and the F2 seeds segregated into 3:1 ratio. The digenic inheritance (9:3:3:1) of cotyledon colour was observed in the orange  light green and yellow  brown crosses, and its epistatic (9:3:4) ratio was obtained when analysed F2 seed derived from yellow  dark green and brown  dark green crosses. The trigenic inheritance pattern, which brought three genes (Y, B, Dg) was observed in light green  dark green cross and produced 27 (orange): 9 (yellow): 9 (brown): 3 (light green): 16 (dark green) ratio. The two genes (Y and B) are responsible for producing yellow and brown, respectively cotyledon colour. The orange colour of cotyledon was received in the dominant homozygous condition (YYBB), but remains green in the double recessive homozygous (yybb) situation. A third gene ‘Dg’ was responsible to block the synthesis of both pigments in recessive state and dark green cotyledons.